FORMULASI DAN UJI SIFAT FISIK MASKER ANTIJERAWAT DARI EKSTRAK SABUT KELAPA ( Cocos nucifera L) - Fauziah, Fauziah; Marwarni, Rima; Adriani, Azmalina (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2020)
Coconut is a multipurpose tree for people in the tropics. Almost all parts can be used such as leaves, fruit, stems, and roots. Besides having many benefits of coconut, it also produces waste from its fruit, namely coconut fiber. Coconut coir has a very high tannin content. In general, tannin compounds can be indicated as anti-inflammatory, and anti-bacterial. The purpose of this study was to formulate the anti-acne mask from coconut coir extract and to test its physical properties. This study uses an experimental research method, in which three mask formulas are made with variations in the concentration of active substances and polyvinyl alcohol (PVA). In this study the active substance used was coconut coir extract. The formulas used are formulas A, B, and C with the concentration of active substances successively as follows: 1%, 2%, 4%. The results of research that have been carried out that the mask formula that has the best physical properties is formula B, because it fulfills the physical properties provisions of the peel off face mask including organoleptic, homogeneity, pH, dispersal power, and drying time.